2011
DOI: 10.1016/j.jaac.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Abstinence: National Institute of Drug Abuse Multisite Buprenorphine/Naloxone Treatment Trial in Opioid-Dependent Youth

Abstract: Objective To examine predictors of opioid abstinence in buprenorphine/naloxone (Bup/Nal) assisted psychosocial treatment for opioid dependent youth Method Secondary analyses of data from 152 youth (ages 15–21) randomly assigned to 12 weeks of extended Bup/Nal therapy or up to 2 weeks of Bup/Nal detoxification, both with weekly individual and group drug counseling. Logistic regression models were constructed to identify baseline and during-treatment predictors of opioid positive urines (OPU) at week-12. Predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 28 publications
2
49
2
Order By: Relevance
“…It is associated with better outcomes in youth (Subramaniam et al, 2011;Woody et al, 2008) and adults (Armstrong et al 2010;Mintzer et al, 2007). Adult studies examining long term treatment with BUP/NAL revealed a 39 to 63% program retention rate at 6 months, and 53% at 1 year (Fiellin et al, 2006;Armstrong et al, 2010;Fiellin et al, 2008).…”
Section: Program Retentionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is associated with better outcomes in youth (Subramaniam et al, 2011;Woody et al, 2008) and adults (Armstrong et al 2010;Mintzer et al, 2007). Adult studies examining long term treatment with BUP/NAL revealed a 39 to 63% program retention rate at 6 months, and 53% at 1 year (Fiellin et al, 2006;Armstrong et al, 2010;Fiellin et al, 2008).…”
Section: Program Retentionmentioning
confidence: 99%
“…Rates of treatment retention in adolescents were reported 72% at 4-weeks in a randomized clinical trial (Marsch et al, 2005), and 50% at day 30 and 25% at day 132 in a retrospective chart review (Bell & Mutch, 2006). Opiate users aged 15-21 in BUP/NAL treatment had a 3-month retention rate of 70% in a multisite trial (Woody et al, 2008) and of 44% in a randomized trial (Subramaniam et al, 2011). Warden et al (2012) reported a treatment retention rate of 92% at 4-weeks, 78% at 8-weeks and 72% at 12-weeks in youth aged 15-21.…”
Section: Treatment Retentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subramaniam et al (2011) evaluated predictors of abstinence from National Institute on Drug Abuse (NIDA) multisite bup/nal treatment trial in opioid-dependent youth. They found that youth reporting injection drug use, and those receiving adjuvant treatments for additional health problems, were more likely to have a lower opioid use.…”
Section: Discussionmentioning
confidence: 99%